(25b-4)-6(4b+3)=-3

Simple and best practice solution for (25b-4)-6(4b+3)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (25b-4)-6(4b+3)=-3 equation:


Simplifying
(25b + -4) + -6(4b + 3) = -3

Reorder the terms:
(-4 + 25b) + -6(4b + 3) = -3

Remove parenthesis around (-4 + 25b)
-4 + 25b + -6(4b + 3) = -3

Reorder the terms:
-4 + 25b + -6(3 + 4b) = -3
-4 + 25b + (3 * -6 + 4b * -6) = -3
-4 + 25b + (-18 + -24b) = -3

Reorder the terms:
-4 + -18 + 25b + -24b = -3

Combine like terms: -4 + -18 = -22
-22 + 25b + -24b = -3

Combine like terms: 25b + -24b = 1b
-22 + 1b = -3

Solving
-22 + 1b = -3

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '22' to each side of the equation.
-22 + 22 + 1b = -3 + 22

Combine like terms: -22 + 22 = 0
0 + 1b = -3 + 22
1b = -3 + 22

Combine like terms: -3 + 22 = 19
1b = 19

Divide each side by '1'.
b = 19

Simplifying
b = 19

See similar equations:

| 9x+5x+4+9=7x+4+6x | | o=6a^2*5 | | 1+x^3=15+x | | 6x+1=(x-22) | | -2((16)+1)+3(16)=14 | | ln(2x+9)=0 | | 9+14s-8=9s+109-7s | | 13-9(x)=11+7(x) | | 3x(x-5)+7(x-5)=0 | | 0.7w-0.3w+0.1w=2 | | x-33=-16 | | 10=8(3(22)-4)-23(22)+20 | | y=3x^2+2x-1 | | -5x^2+6x-1=0 | | 9x^2-5=0 | | g(n)=17n^3-13n^2+10n+2000 | | x=17x^3-13x^2+10x+2000 | | T(n)=17n^3-13n^2+10n+2000 | | n=17n^3-13n^2+10n+2000 | | 9x-5+2x+4= | | log(4)(5x-3)=3 | | -5r^2+6r-1=0 | | 4c+8-c=8+2c | | x^2-3x=x(4+x) | | 9s^2-25=0 | | y=4x^2-3 | | 7y+2=2y+4y+2 | | 2t-7t=15 | | 6(-2+1)=-11(x+1) | | (9b-7)-2(4b+4)=-5 | | 1+15=a | | 9x+4x+4+9=7x+3+5x |

Equations solver categories